Sharing Circles: An Indigenous Methodological Approach for Researching with Groups of Indigenous Peoples. Issue 3 (November 2016) - Tachine, Amanda R.; Bird, Eliza Yellow; Cabrera, Nolan L.
We employed sharing circles as an Indigenous research methodology approach to understand the stories of Native American students as they transitioned into college. We found recognition, responsibility, and relationships as anchors in incorporating Tribal cultural protocol in research. Through trust and vulnerability, Native students shared in-depth personal stories. Attempting to decolonize methodological space is complex, and we provide an accounting of how we maneuvered through this process while offering examples of the rich stories that students shared. As Native scholars, we conclude by considering our cultural and ethical responsibilities as well as the complex tensions that surface as an "insider" and "outsider" when researching and using sharing circles as an Indigenous methodological approach.